Quantification of Internal Carotid Artery Flow with Digital Subtraction Angiography: Validation of an Optical Flow Approach with Doppler Ultrasound - Mendes Pereira, V.; Ouared, R.; Brina, O.; Bonnefous, O.; Satwiaski, J.; Aerts, H.; Ruijters, D.; van Nijnatten, F.; Perren, F.; Bijlenga, P.; Schaller, K.; Lovblad, K.-O. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Digital subtraction angiography is the reference standard technique to evaluate intracranial vascular anatomy and used on the endovascular treatment of vascular diseases. A dedicated optical flow-based algorithm was applied to DSA to measure arterial flow. The first quantification results of internal carotid artery flow validated with Doppler sonography are reported. MATERIALS and METHODS: We included 22 consecutive patients who underwent endovascular procedures. To assess the sensitivity of the algorithm to contrast agent-blood mixing dynamics, we acquired high-frame DSA series (60 images/s) with different injection rates: 1.5 mL/s (n = 19), 2.0 mL/s (n = 18), and 3.0 mL/s (n = 13). 3D rotational angiography was used to extract the centerline of the vessel and the arterial section necessary for volume flow calculation. Optical flow was used to measure flow velocities in straight parts of the ICAs; these data were further compared with Doppler sonography data. DSA mean flow rates were linearly regressed on Doppler sonography measurements, and regression slope coefficient bias from value 1 was analyzed within the 95% confidence interval. RESULTS: DSA mean flow rates measured with the optical flow approach significantly matched Doppler sonography measurements (slope regression coefficient, b = 0.83 ± 0.19, P = .05) for injection rate = 2.0 mL/s and circulating volumetric blood flow <6 mL/s. For injection rate = 1.5 mL/s, volumetric blood flow <3 mL/s correlated well with Doppler sonography (b = 0.67 ± 0.33, P = .05). Injection rate = 3.0 mL/s failed to provide DSA–optical flow measurements correlating with Doppler sonography because of the lack of measurable pulsatility. CONCLUSIONS: A new model-free optical flow technique was tested reliably on the ICA. DSA-based blood flow velocity measurements were essentially validated with Doppler sonography whenever the conditions of measurable pulsatility were achieved (injection rates = 1.5 and 2.0 mL/s). OFoptical flowRMSErelative root mean square errorsIRinjection rateCAcontrast agentUSDDoppler sonography3DRA3D rotational angiography